A new posterosuperior screw placement strategy to avoid in-out-in screws in femoral neck fractures - Li, Shi-Jie; Du, Shou-Chao; Hu, Sun-Jun; Chang, Shi-Min; Zhang, Ying-Qi (Frontiers in Surgery, 2023)
Objective: The inverted triangle configuration of the three cannulated screws is the classic fixation method most commonly performed for undisplaced femoral neck fractures in young and geriatric patients. However, the posterosuperior screw has a high incidence of cortical breach, known as an in-out-in (IOI) screw. In this study, we present a novel posterosuperior screw placement strategy to prevent the screw from becoming IOI. Methods: Using computed tomography data and image-processing software, 91 undisplaced femoral neck fractures were reconstructed. The anteroposterior (AP), lateral and axial radiographs were simulated. To simulated the intraoperative screw placement process, participants used three screw insertion angles (0°, 10°, and 20°) to place the screw on the AP and lateral views of the radiograph according to the three established strategies. On the AP radiograph, a screw was placed abutting (strategy 1), 3.25 mm away from (strategy 2), or 6.5 mm away from (strategy 3) the superior border of the femoral neck. On the lateral radiograph, all the screws were placed abutting the posterior border of the femoral neck. Axial radiographs were used to evaluate the screw position. Results: In strategy 1, all the placed screws were IOI regardless of the screw insertion angle. In strategy 2, there are 48.3% (44/91) of IOI screws occurred at a 0 °screw insertion angle, 41.7% (38/91) of IOI screws occurred at a 10 °screw insertion angle, and 42.9% (39/91) of IOI screws occurred at a 20 °screw insertion angle situation. In strategy 3, no IOI screw occurred, and the screw insertion angles did not affect the safety and accuracy of screw placement. Conclusions: Screws placed according to strategy 3 are safe. The reliability of this screw placement strategy is unaffected by a screw insertion angle of less than 20 degrees.